Application of the polymerase chain reaction (PCR) in veterinary diagnostic virology - Belák, S. (Vet Res Commun, 1993)
The polymerase chain reaction has become an important diagnostic tool for the veterinary virologist. Conventional methods for detecting viral diseases can be laborious or ineffective. In many cases PCR can provide a rapid and accurate test. In this article we explain the basic principles of PCR and supply a reference list of its uses in diagnostic veterinary virology.